The Relation Between The Book Of Life With Believers Verse Unbelievers - Elisabeth Sulastri; Sjanette Eveline (Jurnal Didaskalia, 2022)
The first states that the believer's relationship in the book of life is permanently recorded. Jesus emphasized / explained on the status of believers who have been registered in the Book of Life (Luke 10:10, Hebrews 12:23). The Apostle Paul also said that partners in constant and permanent ministry are listed in the Book of Life (Phil. 4:3). The names of erasures from the Book of Life never apply to believers in Christ because believers are secure in Him, kept by the power of God (1 Pet. 1:5) and are safe in the hands of the Father and the Son (John 10:28-30). Second, how do unbelievers relate to our lives? In the book of Psalm 69, is a messianic psalm that describes the suffering of Christ caused by his enemies. Who are the enemies of Christ? Those who reject Him. What David said in Psalm 69:28, about the unbelievers, David said "May they be blotted out of the Book of Life and may they not be recorded as righteous." Why? Because their actions show not only unbelief, but a hard heart condition that prevents repentance from having faith and coming to the Messiah. The methodology used in writing this article is to study the original language words, text analysis, and interpretation to get the meaning as desired by the author. By means of theological interpretation, translation and analysis of the study of native language words. The Book of Life, especially in Daniel 12:1, has the purpose of protecting those listed in the Book of Life when tribulation comes. The Book of Life implicitly benefits those listed by providing protection to escape this great tribulation. However, for those who are not recorded in us life will suffer various punishments from God. Therefore, the names recorded in the Book of Life must be understood from, namely to protect entry into the Millennium Kingdom and enjoy all the blessings there.